α-MnS nanoparticles in-situ anchored in 3D macroporous honeycomb carbon as high-performance anode for Li-ion batteries - Zhu, S. Y. (2023)
Low electronic/ionic conductivity and huge volume variation severely affect lithium storage performance of MnS. This study is focused on addressing these challenges of MnS through novel synthesis strategy and composite structure: Construction of 3D macroporous honeycomb carbon based on the hard template method of SiO2 microspheres, chemical reaction between KMnO4-carbon, and in-situ gaseous sulfidation. Material characterization demonstrates that α-MnS nanoparticles with a size of 20–30 nm are grown in 3D macroporous honeycomb carbon through chemical bonding. The composite delivers enhanced specific capacity and cycling durability (1048 mAh g−1 at 0.2 A g−1 after 120 cycles, 672 mAh g−1 at 0.5 A g−1 after 200 cycles, 616 mAh g−1 at 2 A g−1 after 200 cycles), and outstanding rate capability (1105 mAh g−1 at 0.1 A g−1, 126 mAh g−1 at 10 A g−1). The composite demonstrates excellent kinetics properties, including high proportion of the capacitive effect, low reaction impedance and high ionic diffusion coefficient. Good structural stability is confirmed by SEM and TEM images. The exceptional electrochemical performance is attributed to the smart design of α-MnS nanoparticles confined in the closed macroporous honeycomb carbon, which improves conductivity and stability of α-MnS.